STRATEGI KOMUNIKASI PEMASARAN : MENGOPTIMALKAN PENGARUH DIGITAL DALAM MENCAPAI TUJUAN BISNIS DI TOKO TYAS GALLERY - Jamilah, Latifatul; Widiarti, Dian; Fitria, Ulfi Nurul; Ningsih, Busri Wahyu; Urriyah, Hilyatul (Fakultas Ekonomi dan Bisnis, 2024)
Tyas Gallery is a business operating in the fashion and printing sectors. Tyas Gallery has a unique advantage to survive in an increasingly competitive business situation. This research uses a descriptive qualitative approach. Data collection methods in this research are divided into two, namely primary data collection and secondary data collection. In terms of marketing communications, Tyas Gallery uses promotional tools including sales promotions, direct marketing, public relations, and word of mouth to optimize its business goals. Tyas Gallery makes full use of online media such as Facebook and WhatsApp to attract consumers. Online media is considered cheaper, more practical and effective in attracting customers.